The Role of Data in Enhancing Municipal Waste Management: Insights from Madhyapur Thimi and Surya Binayak Municipality of Nepal - Baral, Anil Kumar (Journal of Advanced Academic Research, 2024)
In every developing country like Nepal, effective waste management is a major challenge for all municipalities, The Municipalities are the legitimate body to handle all kinds of waste in Nepal which has limited technical capacity and often results in inefficient practices. This study analyzes the waste profiles of wards 2, 3, 4, 5, 6, and 7 in Madhyapur Thimi and wards 2, 3, and 4 in Surya Binayak, Bhaktapur District. This article aims to focus on identifying detailed analytical waste management solutions by examining waste characteristics in detail. It tried to categorized waste into more than 25 distinct types and 19 consolidated types which were collected from 15,000 households daily. The research provides valuable insights for selecting the right machines and methods to improve waste management. The study focuses on 15 key areas, including identifying suitable waste management methods, optimizing collection and transportation efficiency, and assessing infrastructure needs. The research demonstrates that a data-driven approach, grounded in a deep understanding of waste profiles, is essential for selecting the most effective technologies for recycling, composting, or waste-to-energy solutions. Additionally, the findings highlight the importance of public education and community engagement in promoting sustainable waste practices. The study presents specific strategies to meet the unique needs of each municipality. It highlights the importance of municipalities evaluating the costs and regulatory requirements of their waste management practices to ensure that investments in infrastructure and technology are both cost-effective and environmentally responsible. Ultimately, this research advocates for a comprehensive approach to waste management, using detailed waste profiles to guide municipal decision-making and enhance long-term sustainability.